Defeciancy Of Puma And Noxa For Melanomagenesis In A Mouse Model Of Melanoma - Phang, Su Ling (2017)
It is commonly believed without sufficient evidence that the impairment of the ability to undergo apoptosis (a mode of programmed cell death) in response to conventional treatment such as cytotoxic drugs, gained melanoma its notorious resistance to therapy. Studies to determine the contribution of the intrinsic apoptosis pathway for melanomagenesis are often deterred by utilisation of in vitro cell culture models and xenograft models. An established mouse model of melanoma, the Cdkn2a -/-, Tyr-HRASG12V, was utilised in this study to obviate limitations posted by the usage of in vitro and xenograft models.